2008
DOI: 10.1007/s00277-008-0566-9
|View full text |Cite
|
Sign up to set email alerts
|

Management of infections in patients with chronic lymphocytic leukemia treated with alemtuzumab

Abstract: International audienceInfection is a significant cause of morbidity and death in patients with chronic lymphocytic leukemia (CLL). Increased infectious events may arise from the multiple courses of immunosuppressive therapy and progressive deterioration of a patient's immune system over the course of disease. The humanized, anti-CD52 monoclonal antibody alemtuzumab (Campath or Campath-1H) has shown notable activity for both untreated and fludarabine-refractory CLL. The antibody not only targets malignant cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 64 publications
1
19
0
2
Order By: Relevance
“…At the dose used, valganciclovir did not exert any toxic effect on hematopoietic stem cells: hematopoietic recovery was consistent with the response rate and speed expected for such diseases (manuscript in preparation). In conclusion, while fully agreeing with Elter's conclusions that alemtuzumab treatment deserves an adequate management of infectious risk [1], we have shown that a CMV reactivation prophylaxis may allow the use of alemtuzumab in diseases traditionally considered too risky for such a therapy. We provide evidence that oral valganciclovir is effective as anti-CMV prophylaxis in the specific setting of bone marrow failure patients; the optimal duration of treatment as tailored on CD4+ recovery needs to be assessed in larger confirmatory studies.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…At the dose used, valganciclovir did not exert any toxic effect on hematopoietic stem cells: hematopoietic recovery was consistent with the response rate and speed expected for such diseases (manuscript in preparation). In conclusion, while fully agreeing with Elter's conclusions that alemtuzumab treatment deserves an adequate management of infectious risk [1], we have shown that a CMV reactivation prophylaxis may allow the use of alemtuzumab in diseases traditionally considered too risky for such a therapy. We provide evidence that oral valganciclovir is effective as anti-CMV prophylaxis in the specific setting of bone marrow failure patients; the optimal duration of treatment as tailored on CD4+ recovery needs to be assessed in larger confirmatory studies.…”
supporting
confidence: 89%
“…Dear Editor, Elter et al recently published in your journal a comprehensive report on the management of infectious risk during treatment by alemtuzumab [1]. Their paper referred exclusively to chronic lymphocytic leukemia patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A third group was constituted of 11 patients treated with VTd (bortezomib-thalidomide-low-dose dexamethasone) for use as comparison, as this group was collected using high-dose cyclophosphamide (hdCyclo). 6,7 We have excluded patients who might have received other bortezomib-based regimens and who were not collected at front line to homogenize our studied population. The median age at collection was 57, 62 and 60 years; sex ratio was 1.64, 1.21 and 1.20; and median weight was 73, 65 and 72 kg for the three groups, respectively.…”
mentioning
confidence: 99%
“…over 30 min; premedication, infection prophylaxis and monitoring was performed according to actual standards. 7 Diagnosis and restaging was carried out according to the 1996 National Cancer Institute (NCI) criteria. 8 Of the 61 CLL patients recruited from March 2005 to November 2008 in centers across Germany, four patients did not receive therapy owing to withdrawn consent or revision of diagnosis.…”
mentioning
confidence: 99%